Cross-compartment metabolic coupling enables flexible photoprotective mechanisms in the diatom Phaeodactylum tricornutum - Broddrick, Jared T (The New phytologist, 2019)
© 2019 J. Craig Venter Institute New Phytologist © 2019 New Phytologist Trust.